Geographical distribution of MTHFR C677T gene polymorphisms among the reproductive-age women in Chinese Han populations: based on migration - Shen, Yifen; Gu, Yongchun; Tang, Ying; Shen, Hao; Liu, Chao (BMC women's health, 2024)
Background Methylenetetrahydrofolate reductase (MTHFR) is essential for the metabolism of folic acid and homocysteine. The MTHFR C677T polymorphism is associated with several disorders. Our study aims to explore the geographical distributions of the MTHFR C677T polymorphism of women in China and how migration affected the polymorphism in Suzhou. Methods A total of 7188 women of reproductive age were recruited in Suzhou of the study. Subjects were classified according to their native places after data extraction. MTHFR C677T gene polymorphisms were detected by quantitative PCR with genomic DNA isolated from blood samples. Results The frequencies of the 677T allele and 677TT genotype were higher in northern China than that in southern China and decreased in geographical gradients from north to south. The frequencies were considerably higher in the migrant population than that in the indigenous population of Suzhou. The migrant population have gradually changed the prevalence in Suzhou. Conclusions Our study suggested that the prevalence of MTHFR C677T polymorphisms among women varied across different geographical regions in Chinese Han populations. The 677T allele frequencies of the northern populations were significantly higher than those of the southern populations. The migrant population gradually changed the prevalence of the MTHFR C677T polymorphism in Suzhou.